Complexity of Caribbean migration. - CONWAY, Dennis (1994)
Examines the regional system of international mobility, including the importance of intra-regional mobility patterns and patterns of temporary stay-over/visits. Concludes that international circulation, temporary sojourning and repetitive mobility appear as dominant and common patterns throughout the region.